2017
DOI: 10.1093/aje/kwx219
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche and Incidence of Diabetes: A Prospective Study of 300,000 Women in China

Abstract: Previous studies of predominantly Western populations have reported inconsistent associations between age at menarche and risk of diabetes. We examined this relationship among Chinese women, who generally experience menarche at a later age than Western women. In 2004–2008, China Kadoorie Biobank recruited 302,632 women aged 30–79 years from 10 areas across China, and recorded 5,391 incident cases of diabetes during 7 years of follow-up among 270,345 women without baseline diabetes, cardiovascular disease or ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…Findings from this collaboration of population-based cohort studies of women's health add to the accruing evidence that characteristics of a woman's reproductive history may be associated with incident diabetes in later life. Consistent with previous studies 13,14,26,27 early menarche (≤11 years) was associated with a small increase in risk of diabetes compared with menarche at 13 years; however, our findings indicate that the effect is only apparent among women with a midlife Initiative, 27 a large study of hormone replacement therapy in postmenopausal women, the inverse association between age at menarche and risk of diabetes was attenuated once adjustment was made for BMI in adult life (as we also found). The discrepancy between these two large studies may be a birth cohort effect or may be attributable to the use of different categories for menarche age, and it would be of interest to know whether stratification by BMI in these studies would yield findings similar to ours.…”
Section: Discussionsupporting
confidence: 92%
“…Findings from this collaboration of population-based cohort studies of women's health add to the accruing evidence that characteristics of a woman's reproductive history may be associated with incident diabetes in later life. Consistent with previous studies 13,14,26,27 early menarche (≤11 years) was associated with a small increase in risk of diabetes compared with menarche at 13 years; however, our findings indicate that the effect is only apparent among women with a midlife Initiative, 27 a large study of hormone replacement therapy in postmenopausal women, the inverse association between age at menarche and risk of diabetes was attenuated once adjustment was made for BMI in adult life (as we also found). The discrepancy between these two large studies may be a birth cohort effect or may be attributable to the use of different categories for menarche age, and it would be of interest to know whether stratification by BMI in these studies would yield findings similar to ours.…”
Section: Discussionsupporting
confidence: 92%
“…Early menarche is associated with reduced insulin sensitivity and higher glucose,1, 2, 3, 4, 5, 6, 7, 8, 9 higher triglycerides and cholesterol levels,2, 6, 10 higher blood pressure,4, 5, 11, 12 and greater waist circumference and body mass index (BMI) 4, 5, 13, 14, 15. In line with these findings, there is some but less consistent evidence of an association between age at menarche and cardiovascular disease (CVD) events 12, 16, 17, 18.…”
mentioning
confidence: 99%
“…12 The few observational analyses that were able to adjust for childhood adiposity found that the associations of age at menarche with adult cardiometabolic health were virtually completely attenuated, suggesting that childhood adiposity is a key confounder. 4,14 However, studies from populations in which childhood obesity is less prevalent, such as Korea, 5,7,8 Bangladesh, 6 China, 9 and Brazil, 10 also indicate an association between early menarche and worse cardiometabolic health.…”
mentioning
confidence: 99%
“…Comparison of the associations between puberty timing and T2D with and without adjustment for adiposity would be informative. Furthermore, a recent study from China reported that the association between AAM and incident diabetes differed by year of birth, with a stronger association observed in women who were born in more recent decades [12]. Such potential effect modifications were not investigated in the previous meta-analysis [11].…”
Section: Introductionmentioning
confidence: 98%
“…That review identified 10 relevant publications (315,428 participants) dated until the end of 2013 and included only 2 studies in non-Western settings (both were from China) [11], which did not allow for comparisons between regions. There have been several very large Asian studies published subsequently [12,13]. More importantly, this previous meta-analysis analysed only effect estimates adjusted for body mass index (BMI) [11].…”
Section: Introductionmentioning
confidence: 99%